Correlation between obesity with atopy and family history of atopy in children - Putria Rayani Apandi; Budi Setiabudiawan; Abdurachman Sukadi (Indonesian Pediatric Society, 2011)
Background The prevalence of childhood obesity and atopy has increased in recent decades. Research on links between obesity and atopy has shown varied results. Few previous studies have reported on the significance of family history of atopic disease in children.Objective To determine correlation between obesity with atopy and family history of atopic disease in children.Methods This cross-sectional study was conducted from April to September 2010 in the Pediatric Allergy-Immunology subdivision, Hasan Sadikin Hospital. Children aged 6âˆ’11 years were divided into four groups of 40 each: obese subjects with and without family history of atopic disease, and normal weight subjects with and without family history of atopic disease. Skin prick test was performed to determine which subjects had atopy. Chi-square test was used to analyze mutual independence, and partial Chi-square test was used to analyze correlation of obesity to atopy and family history of atopic disease in children. Environmental factors, type of childbirth, and pregnancy history were also analyzed as risk factors for atopy.Results Of 80 obese children with and without family history of atopic disease, 40 (100%) and 38 (95%), respectively, were atopic. Of 80 normal weight children with and without family history of atopic disease, 39 (98%) and 9 (23%), respectively, were atopic. Thus atopy was observed in 126 subjects, while the remaining 34 subjects were non-atopic. Partial test showed a correlation between obesity with atopy and family history of atopic disease (P < 0.001). There were no significant differences in risk factors for atopy by group.Conclusion Obesity correlates with atopy and family history of atopic disease in children.